Seed production potentiality in yield and quality of eggplant (Solanum melongena L.) Grown under summer and winter seasons (Bangladesh Journal of Agricultural Research, 2017)
Two separate field experiments were conducted at the Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during April to October 2012 (summer season) and October 2012 to March 2013 (winter season) to evaluate and compare the seasonal effect on fruit set, seed yield and seed quality of eggplant. Six eggplant varieties (BARI Begun-1, BARI Begun-5, BARI Begun- 6, BARI Begun-8, BARI Begun-9 and Khotkhotia) were grown separately with proper isolation in both the seasons. Significant variation in fruit set per plant, seed yield per fruit and seed quality of eggplant were observed due to execution of growing seasons. The highest seed yield per fruit was obtained from BARI Begun-6 in both the seasons. Number of fruits per plant, seeds per fruit and 1000-seed weight showed the highest in winter season (October to March) as a result the highest seed yield was obtained from the same season. Winter season also showed the best seed quality attributes like germination (%), co-efficient of germination and vigour index irrespective of variety used. Based on seed yield and seed quality, winter season (October to March) found to be more favourable for quality seed production of eggplant in Bangladesh condition.Bangladesh J. Agril. Res. 42(3): 437-446, September 2017